Does Pandemic A/H1N1 Virus Have the Potential To Become More Pathogenic? - Natalia A. Ilyushina (American Society for Microbiology, 2010)
ABSTRACT Epidemiologic observations that have been made in the context of the current pandemic influenza virus include a stable virulence phenotype and a lack of propensity to reassort with seasonal strains. In an attempt to determine whether either of these observations could change in the future, we coinfected differentiated human airway cells with seasonal oseltamivir-resistant A/New Jersey/15/07 and pandemic A/Tennessee/1-560/09 (H1N1) viruses in three ratios (10:90, 50:50, and 90:10) and examined the resulting progeny viruses after 10 sequential passages. When the pandemic virus was initially present at multiplicities of infection equal to or greater than those for the seasonal virus, only pandemic virus genotypes were detected. These adapted pandemic strains did, however, contain two nonsynonymous mutations (hemagglutinin K154Q and polymerase acidic protein L295P) that conferred a more virulent phenotype, both in cell cultures and in ferrets, than their parental strains. The polymerase acidic protein mutation increased polymerase activity at 37°C, and the hemagglutinin change affected binding of the virus to α2,6-sialyl receptors. When the seasonal A/H1N1 virus was initially present in excess, the dominant progeny virus was a reassortant containing the hemagglutinin gene from the seasonal strain and the remaining genes from the pandemic virus. Our study demonstrates that the emergence of an A/H1N1 pandemic strain of higher virulence is possible and that, despite their lack of detection thus far in humans, viable seasonal/pandemic virus reassortants can be generated. IMPORTANCE This report supplies a key piece of information for investigating future evolution scenarios of pandemic A/H1N1 influenza in the human population. We report that the emergence of an A/H1N1 pandemic strain of higher virulence is possible and that, despite their lack of detection thus far in humans, viable seasonal/pandemic virus reassortants can be generated.